Productivity and input efficiencies of FIRB planted wheat as influenced by nitrogen levels under deficit irrigation - KUMAR, PARVEEN; KUMAR, ANIL; KUMAR, ROHTAS; SEWHAG, MEENA (Journal of Soil and Water Conservation, 2023)
Field experiment was conducted during the rabi (winter) seasons of 2018-19 and 2019-20 to assess the productivity and input efficiencies of FIRB planted wheat (Triticum aestivum (L.) as influenced by nitrogen levels under deficit irrigation on sandy loam soil at CCS Haryana Agricultural University, Hisar. The experiment consisted of 12 treatment combinations with three irrigation methods viz. wheat crop was sown on bed and irrigation was applied in every furrow irrigation (FIRBS sowing with every furrow irrigation), wheat crop was sown on bed and irrigation was applied in alternate furrow i.e. application of irrigation by skipping one furrow (FIRBS sowing with alternate furrow irrigation) and Flat sowing with flood irrigation(conventional method or farmer practice) assisted in main plots and four nitrogen levels viz. control, 80, 90 and 100 percent RDN assisted in sub plots. The experiment was conducted in split plot design with four replications. The pooled analysis of the data showed that significantly higher number of effective tillers per metre row length, grains per spike and grain yield were registered under FIRB sowing with every furrow irrigation method over flat sowing with flood irrigation (conventional method or farmer practice) and FIRB sowing with alternate furrow irrigation method. The flat sowing with flood irrigation (conventional method) and FIRB sowing with alternate furrow irrigation method did not differ significantly in respect of yield attributes and yield. FIRB planting with every furrow irrigation method produced 17.37 and 13.93 percent higher yield over FIRB planting with alternate furrow irrigation and flat sowing with flood irrigation, respectively. Among nitrogen levels, highest values of nitrogen uptake, yield attributes and yield were found with the application of 100 per cent RDN as compared to control and lower levels. Higher economic nitrogen use efficiency was found under FIRB planting with every Furrow irrigation method as compared to FIRBS sowing with alternate furrow irrigation and Flat sowing with flood irrigation; however, different nitrogen levels did not differ significantly in this respect.